DEVELOPMENT OF ADSORBENTS FROM RICE HUSK FOR CESIUM REMOVAL FROM SIMULATED WASTE WATER USING CENTRAL COMPOSITE DESIGN (FUDMA JOURNAL OF SCIENCES, 2023)
This paper deals with the production of adsorbents and adsorption studies for the uptake of Cesium (Cs) ions from aqueous solutions using carbonized rice husk composite as adsorbent. The carbonized rice husk and surface properties of the adsorbent were characterized by Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and Brauner Emmet and Teller (BET) analyzer. Central Composite Design (CCD) was used to optimize the process variables such as initial metal ion concentration, Contact time, adsorbent dosage and pH of the solution on the performance of percentage removal and adsorption capacity. The experimental data were validated with different isotherms and kinetic models to assess the solute interaction behavior and nature of adsorption. The maximum adsorption capacity for (a) rice husk (8.03mg/g) and impregnated rice husk (b) (13.58 mg/g) adsorbents were fully evaluated. Revealing the reliability and suitability of the optimization approach .In addition, the results of isotherm study show that the Langmuir model can be used to best describe the adsorption behavior of Cs on to the rice husk and impregnated rice husk composite s adsorbents
Keywords: Central composite design, Impregnation, Cesium, adsorption, adsorbent, Concentration.